Comprehensive Identification and Expression Profiling of Circular RNAs During Nodule Development in Phaseolus vulgaris - Wu, Zhihua; Huang, Wen; Qin, Erdai; Liu, Shuo; Liu, Huan; Grennan, Aleel K.; Liu, Hong; Qin, Rui (Frontiers in Plant Science, 2020)
Symbiotic nitrogen fixation by legume nodules provides an abundant nitrogen source for plants, and understanding this process is key for developing green agriculture. Circular RNA (circRNA), a type of endogenous RNA produced by reverse splicing of mRNA precursors, plays important regulatory roles in plants at the transcriptional and post-transcriptional levels. However, the relationship between circRNAs and nodulation in legumes is unknown. Nodulation consists of three main stages: early infection thread formation, nodule formation, and nitrogen fixation. Here, we performed comprehensive identification and expression profiling of circRNAs during the three stages of nodulation in common bean (Phaseolus vulgaris) compared to uninoculated roots of corresponding ages by constructing circRNA-Seq and mRNA-Seq libraries of roots and nodules. We identified 8,250 circRNAs with high confidence, 3,200 of which were specifically produced during nodulation, with the highest number at the nitrogen fixation stage. Significantly more circRNAs were derived from exons than from intergenic regions or introns in all samples. The lengths and GC contents of the circRNAs were similar in roots and root nodules. However, circRNAs showed specific spatiotemporal expression patterns during nodule and root development. GO and KEGG enrichment analysis of parental genes of differential expressed circRNAs at the three stages indicated their involved in different biological processes. For example, “oxidation−reduction process”, “TOR signaling” and “transporter activity” were uniquely enriched among parental genes of upregulated cicrRNAs during early infection thread formation, nodule formation and nitrogen fixation, respectively. Almost all of the circRNAs showed the positive correlation to parental genes, indicating that they positively regulated expression of their parental genes. Of the 8,250 circRNAs, we identified miRNA binding sites for 4,607 (55.8%), but not for the remaining 3,643 (44.2%). We confirmed that 12 differentially expressed circRNAs might function as miRNA sponges during nodule development, such as photosynthesis during nodule formation and nitrogen assimilation during nitrogen fixation. These findings thus provide an important theoretical basis for understanding the mechanisms employed by circRNAs in legumes during nodulation.